Drug Information and Pharmacotherapy 2015
DOI: 10.1136/ejhpharm-2015-000639.202
|View full text |Cite
|
Sign up to set email alerts
|

DI-024 Off-label use of gabapentin and pregabalin in a tertiary hospital

Abstract: BackgroundGabapentin and pregabalin are two GABA analogues, example of an evergreening strategy. Both have been associated with a markedly off-label use.PurposeTo describe the extent and nature of the off-label use of gabapentin and pregabalin.Material and methodsProspective observational study performed in a tertiary hospital. We included patients being treated with gabapentin or pregabalin at any time between June and August 2014. The variables collected were: sex, age, drug, therapeutic indication, dose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Approximately one in 10 patients had their gabapentinoid therapy discontinued during their admission. This rate is similar to that reported by Gingras et al 13 There are reports of withdrawal symptoms following abrupt discontinuation of these agents. 22 Ceasing abruptly can result in anxiety, insomnia, headache, sweating, nausea and diarrhoea.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Approximately one in 10 patients had their gabapentinoid therapy discontinued during their admission. This rate is similar to that reported by Gingras et al 13 There are reports of withdrawal symptoms following abrupt discontinuation of these agents. 22 Ceasing abruptly can result in anxiety, insomnia, headache, sweating, nausea and diarrhoea.…”
Section: Discussionsupporting
confidence: 91%
“…Such use has been reported by other researchers. 12,13 The high incidence of off-label prescribing noted in this study also raises issues related to the costs incurred by the patient when their care is transferred to primary care, as only approved indications are reimbursed under the Pharmaceutical Benefits Scheme (PBS). Legally, a private prescription would be required for an off-label indication, otherwise supply would be considered fraudulent if written by their General Practitioner on a PBS prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Off-label use includes management of a wide range of conditions such as bipolar disorder, complex regional pain syndrome, attention deficit disorder, restless legs syndrome, periodic limb movement, sleep disorders, headaches, alcohol withdrawal syndrome, chronic back pain, fibromyalgia, visceral pain and acute postoperative pain. 4,5 The rate of new prescriptions is increasing and tripled in England from 2007 to 2017. 6 Pregabalin prescriptions in England increased from 2.7 million scripts in 2013 to 7 million scripts in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…8 Gabapentin has a long history of off-label prescription. 9 Between 1998 and 2000, a study involving 105 Medicaid patients who were prescribed gabapentin found that 95% of prescriptions had been for off-label indications. 10 A number of these indications were for psychiatric illness, including bipolar disorder (10% of all prescriptions in the study) and anxiety disorders.…”
Section: It Wasmentioning
confidence: 99%